2020
DOI: 10.1007/s13300-020-00967-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct Medical Costs of Incident Complications in Patients Newly Diagnosed With Type 2 Diabetes in China

Abstract: Introduction Reliable country-specific incidence and cost data on diabetes-related complications are essential inputs for the projections of the economic burden of diabetes. The aim of this study was to provide patient-level cost estimates of managing and treating complications in patients newly diagnosed with type 2 diabetes mellitus (T2DM) in China. Methods Patients newly diagnosed with T2DM in the Tianjin Urban Employee Basic Medical Insurance Claims database between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This patient population is expected to increase to approximately 212 million by 2045 1 . Type 2 diabetes generally imposes a substantial burden on healthcare systems globally as it results in a high demand for healthcare resources and high associated costs [1][2][3][4] , and East Asia is no exception [5][6][7][8][9][10][11][12][13] . Hospital inpatient care is the largest component of medical expenditure in type 2 diabetes, with one study estimating that hospitalization accounted for 43% of total medical costs 14 .…”
Section: Introductionmentioning
confidence: 99%
“…This patient population is expected to increase to approximately 212 million by 2045 1 . Type 2 diabetes generally imposes a substantial burden on healthcare systems globally as it results in a high demand for healthcare resources and high associated costs [1][2][3][4] , and East Asia is no exception [5][6][7][8][9][10][11][12][13] . Hospital inpatient care is the largest component of medical expenditure in type 2 diabetes, with one study estimating that hospitalization accounted for 43% of total medical costs 14 .…”
Section: Introductionmentioning
confidence: 99%
“…For complications that were not reported by Duan et al., we used estimates derived from urban populations reported by He et al. for neuropathy and retinopathy, 26 and Wang et al. for amputation.…”
Section: Methodsmentioning
confidence: 99%
“…A recent survey of heart failure alone in China estimated a mean per-capita cost of USD 4407 for inpatients, and a 2012 estimation reported that heart failure total costs were USD 5.42 billion, indicating a severe burden on a country where even a 1.10% estimated prevalence translates into millions of patients [52,57]. A 2020 study on the direct costs of diabetes in management and subsequent heart, cerebral, and vascular diseases reported costs of USD 109 billion in 2019, increased care costs of up to USD 2847 per person during care for the first myocardial infarction, and a peak cost age range from 70 to 80 years old [58]. For obesity, a scoping meta-analysis of the time period from 2010-2020 found direct medical costs of between USD 8.4 and 23.9 billion but with additional indirect costs (facility, supply, record keeping, etc.)…”
Section: Public Health Costs: Fundingmentioning
confidence: 99%